Flavonol glycosides from the leaves of Fissistigma pallens (Fin. & Gagn.) Merr. - Thinh, Ngo Sy; Thu, Nguyen Thi Bich; Khoi, Nguyen Minh; Ngoc, Tran Minh; Tai, Bui Huu; Kiem, Phan Van; Nhiem, Nguyen Xuan (Vietnam Journal of Science and Technology, 2020)
Using combined chromatographic methods, five flavonol glycoside compounds including: kaempferol 3-rutinoside (1), rutin (2), kaempferol 3-O-α-L-rhamnopyranosyl-(1→6)-β-D-galactopyranoside (3), isorhamnetin 3-robinobioside (4), and kaempferol 3-O-α-L-rhamnopyranosyl-(1→2)-β-D-galactopyranoside (5) were isolated from the methanol extract of the leaves of Fissistigma pallens (Fin. & Gagn.) Merr. Their chemical structures were determined using NMR spectra as well as in comparison with the reported data.